2013
DOI: 10.1557/opl.2013.1000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sodium-containing substrates on Kesterite CZTSSe thin films based solar cells

Abstract: This work deals with the influence of sodium on the properties of CZTSSe material and solar cells. For that purpose, two types of substrates are compared, one with low sodium content (borosilicate glass), the other one with higher sodium content (soda-lime glass). In each case the Na-content in the CZTSSe passing from the substrate through the Mo back contact is quantified by secondary ion mass spectroscopy analysis. Photoluminescence spectroscopy indicates that better quality material is achievable when incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…Moreover, an increased hole density and a shift in acceptor defect energy making them shallower has been reported by Li et al which should be the reason for an increase in open‐circuit voltage ( V oc ) and fill factor (FF) observed in various studies .…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, an increased hole density and a shift in acceptor defect energy making them shallower has been reported by Li et al which should be the reason for an increase in open‐circuit voltage ( V oc ) and fill factor (FF) observed in various studies .…”
Section: Introductionmentioning
confidence: 73%
“…Compared to CIGSe only little has been published about the influence of sodium and potassium on CZTSSe so far , but due to the systematic relationship between kesterite and chalcopyrite semiconductors similar trends are also expected for the kesterites. First studies confirm this assumption even though the exact way how sodium acts within the absorbers is still not fully understood – not even for chalcopyrite absorbers.…”
Section: Introductionmentioning
confidence: 87%
“…Irrespective of substrate choice, the incorporation of alkali dopants in both CIGS and CZTSSe is critical to achieve high performance and this is associated with a reduction in the density of grain boundaries which limit the collection of photo-generated carriers due to non-radiative recombination. For example, the formation of liquid Na 2 Se x phases during annealing has been associated with improved grain growth [3] and favourable formation of (112) crystal facets [4,5], as well as increasing the device open circuit voltage ( V OC ) and fill factor (FF) [6][7][8][9]. The improved V OC is explained as a higher built-in voltage resulting from movement of the bulk Fermi level toward the valence band thereby reducing the influence of deep recombination centres, while higher FF stems from increased bulk CZTSe conductivity with increased hole density and mobility [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that intentional incorporation of sodium (Na) from NaF precursor layers positively affects the photovoltaic performance of CZTS cells . However, the effect of Na on the layers and on the photovoltaic properties of the CZTS cells remains poorly characterized .…”
Section: Introductionmentioning
confidence: 99%